Clinical Usefulness of Magnetic Resonance Imaging in Four Children With Scleroderma - Kazushi AGATA; Hisashi KAWASHIMA; Atsushi KUMADA; Yasuyo KASHIWAGI; Hiroko HARA (Archives of Rheumatology, 2018)
Children with localized scleroderma may have more serious sequelae than adults with the disease. In this case report, we analyzed four girls with localized scleroderma (generalized morphea) to evaluate the clinical usefulness of magnetic resonance imaging in facilitating disease control and investigating patient responsiveness to various treatments. Two of the children had flexion contracture, and two displayed a clear high-intensity area in the bone marrow under the sclerotic skin on magnetic resonance imaging. Two girls had different bilateral circumferences of the legs or forearms. These abnormalities were detected without any obvious changes in blood chemistry. Our results demonstrated that magnetic resonance imaging is useful for the evaluation of treatment effects for localized scleroderma in children.